CBL3 and CIPK18 are required for the function of NHX5 and NHX6 in mediating Li+ homeostasis in Arabidopsis - Zhang, Xiao (Journal of plant physiology, 2020)
Copyright © 2020 Elsevier GmbH. All rights reserved.